Bacterivorous Ciliate Tetrahymena pyriformis Facilitates vanA Antibiotic Resistance Gene Transfer in Enterococcus faecalis - Temilola O. Olanrewaju; James S. G. Dooley; Heather M. Coleman; Chris McGonigle; Joerg Arnscheidt (Antibiotics)
Background: Wastewater treatment plants (WWTPs) are hotspots for the emergence and spread of antibiotic resistance genes (ARGs). In activated sludge treatment systems, bacterivorous protozoa play a crucial role in biological processes, yet their impact on the horizontal gene transfer in Gram-positive enteric bacteria remains largely unexplored. This study investigated whether the ciliate Tetrahymena pyriformis facilitates the transfer of antibiotic resistance genes between Enterococcus faecalis strains. Methods: Conjugation assays were conducted under laboratory conditions using a vanA-carrying donor and a rifampicin-resistant recipient at an initial bacterial concentration of 109 CFU/mL and ciliate density of 105 N/mL. Results: Transconjugant numbers peaked at 2 h when experiments started with recipient bacteria harvested in the exponential growth phase, and at 24 h when bacteria were in the stationary phase. In both cases, vanA gene transfer frequency was highest at 24 h (10−4–10−5 CFU/mL), and the presence of energy sources increased gene transfer frequency by one order of magnitude. Conclusions: These findings suggest that ciliate grazing may contribute to vanA gene transfer in WWTP effluents, potentially facilitating its dissemination among permissive bacteria. Given the ecological and public health risks associated with vanA gene persistence in wastewater systems, understanding protozoan-mediated gene transfer is crucial for mitigating the spread of antibiotic resistance in aquatic environments.